On the Meanings of Comprehensive Reparation for Victims of the Colombian Armed Conflict in Ecuador - Moreno Núñez, Paola Natalia (2024)
This essay explores the meanings that victims of the Colombian armed conflict who are in Ecuador develop regarding full reparation, based on their perceptions of dignity and life projects. It is based on the argument that the Victims and Land Restitution Bill (Law 1448) establishes an asymmetry in terms of access to the rights to truth, justice and reparation with guarantees of non-repetition, as well as to the support measures established in this law, between victims within Colombian territory and people who, being survivors of the conflict, have fled to other countries. Hence, adverse conditions derive for the people’s dignity and life projects to be restored. This becomes even more evident when living conditions in Ecuador exclude and marginalize Colombian refugees. It is therefore urgent to analyze reparation measures that are not necessarily bound to government responses, which, due to their nature and institutional competencies, are limited to Colombian territory. There is a manifest need for reparation measures to take into account the expectations of permanence in Ecuador of Colombian victims of the conflict who are seeking to rebuild their life projects in this country.